2012
DOI: 10.1007/s12262-012-0451-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Serum Creatinine, Creatine Kinase and Urinary Myoglobin in Detecting Acute Renal Failure due to Rhabdomyolysis in Trauma and Electrical Burns Patients

Abstract: Rhabdomyolysis due to trauma and burns is an important cause of acute renal failure (ARF) secondary to myoglobinuria. To prevent morbidity and mortality from ARF due to rhabdomyolysis, early detection of ARF by monitoring the biochemical parameters such as serum creatinine, serum creatine kinase (CK), and urinary myoglobin (UM) can be helpful. The aims of the study were (1) to detect ARF due to rhabdomyolysis using serum creatinine, serum CK, and UM in trauma and electrical burn patients (2) to compare utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Delaney et al recently conducted a retrospective study showing that based on the RIFLE criteria, 59% of the patients with rhabdomyolysis had AKI, most of which were prerenal.35 However, a study by Chen et al found that only 14.4% patients with rhabdomyolysis developed AKI (9). In a recent study of 521 pediatric patients with posttraumatic rhabdomyolysis, AKI occurred in 70 (13.4%) patients (36). In our study based on the AKIN criteria, total of 23 (53.4%) patients developed AKI.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Delaney et al recently conducted a retrospective study showing that based on the RIFLE criteria, 59% of the patients with rhabdomyolysis had AKI, most of which were prerenal.35 However, a study by Chen et al found that only 14.4% patients with rhabdomyolysis developed AKI (9). In a recent study of 521 pediatric patients with posttraumatic rhabdomyolysis, AKI occurred in 70 (13.4%) patients (36). In our study based on the AKIN criteria, total of 23 (53.4%) patients developed AKI.…”
Section: Discussionmentioning
confidence: 48%
“…In a prospective observational study by Bhavsar and colleagues examined 50 patients with rhabdomyolysis due to trauma and electrical burns. They identified a cutoff value of CK 3805 U/L to be 76.5% sensitive and 87.9% specific in predicting AKI after 48 h of injury (36). In another important study performed by Brown et al reviewed the case records of 1771 trauma patients with increased CK levels.…”
Section: Discussionmentioning
confidence: 99%
“…The presenting clinical features are myalgia, myoglobinuria, and elevated serum creatine kinase (1)(2)(3). The presence of myoglobin in the urine will produce a dark redbrown pigmentation (3)(4)(5). The function of CK is to convert myocyte creatine phosphate into high-energy phosphate groups (adenosine triphosphate) used in energy requiring reactions (6).…”
Section: Introductionmentioning
confidence: 99%
“…The function of CK is to convert myocyte creatine phosphate into high-energy phosphate groups (adenosine triphosphate) used in energy requiring reactions (6). Degradation of approximately 200 grams of muscle can cause an increase in serum CK (3,6). When the massive myocyte breakdown of cell membranes occurs, other intracellular constituents are released besides myoglobin and CK (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation